Mobile genetic elements as vehicle of resistance genes from wastewater isolates. (29th March 2019) - Nicolau, Bruno; Joadas, Andreia; Maia e Silva, Alexandra; Barroso, Helena; Duarte, Aida
Abstract : Introduction: Nowadays, bacterial resistance to antibiotics is a problem that has been growing in Portugal, Europe and all around the world, with its cause being in the uncontrolled use of antibiotics and the dissemination of resistance genes among different bacteria through nature. Objective: Identification of resistant genes inserted into Class I Integrons in wastewater isolates Materials and methods: 165 isolates (110 from affluent waters and 55 from effluent waters) were studied for antibiotic susceptibility and 101 isolates (63 from affluent and 38 from effluent waters) were selected for screening and identification of resistance genes by PCR reaction and sequencing, using 5'-CS and 3'-CS oligonucleotides as specific primers for conserved segments of Class I Integrons. Results: From residual water analyses the total of 165 isolates were multiresistant to antibiotics used in hospital and ambulatory clinics. Among these isolates, the resistance to Trimethroprim-Sulfamethoxazole and Gentamicin were 61, 2% (101/165) and 46.1% (76/165), respectively. Electrophoresis revealed DNA fragments with sizes ranging from 500 to 2000 base pairs according to the number of genes inserted in Integron. After analysis of sequences were identified 22 genes dfr -type ( dfrA1, dfrA12, dfrA15, dfrA17 and dfrA27) responsible by resistance to Trimethroprim, These genes were found in 14 isolates from affluent and 7 from effluent waters. Also, the resistance to gentamicin were conferred by 19 genes aad-type (aadA1, aadA2 and aadA5) from 12 affluent and 7 effluent isolates. These genes can be found alone or in association with each other in the same Integron. Other genes that confer resistance to other antibiotics have also been found such as: rifampicin (arr-3); β-lactamics (oxa-2) and gene aac(6')-Ib-cr which simultaneously confer resistance to fluorquinolones and aminoglycosides only in isolates from affluent waters. Conclusion: The residual waters, upon arriving at urban wastewater treatment plant, are subjected to a depuration process to eliminate chemical and biological contaminants. However, our study revealed the presence of multiresistant bacteria in effluents, which allows their dissemination in the environment and its impact on public health.